E-Governance in India: Measures for Effectiveness: Exploring the Impact of e-Government on Governance and Service Delivery in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Current activities have shown how the Central Government has implemented Information Communication and Technology (ICT) to transform the conventional workings of the global public sector in order to enhance quality and productivity in the delivery of service to the general public. In the present study, e-Government practices bring about openness and accountability, leading to bureaucracy and corruption in public sector organizations, reducing the role of bureaucracy and providing efficient, efficient and effective service to the public. The technological developments in policy sectors across the world have utilized almost equivalent ideas and methods for delivering online services to the people in e-Government and e-Bureaucratic structures. In this paper I want to discuss the usefulness of e-Government for government agencies and the citizens.